2010
DOI: 10.1590/s0100-879x2010007500029
|View full text |Cite
|
Sign up to set email alerts
|

Bradysia hygida (Diptera, Sciaridae) presents two eukaryotic Elongation Factor 1A gene homologues: partial characterization of the eukaryotic Elongation Factor 1A-F1 gene

Abstract: Elongation factor 1A is a highly conserved protein that participates in translation. We report the occurrence of two genes homologous to the eukaryotic Elongation Factor 1A in Bradysia hygida and describe the partial cloning and characterization of the B. hygida eukaryotic Elongation Factor 1A-F1 (BheEF1A-F1) gene. The pattern of BheEF1A-F1 expression in the salivary gland at the end of the fourth larval instar was investigated using real-time PCR. The results showed that BheEF1A-F1 expression levels are relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Total RNA was isolated from salivary glands (10 pairs), prothoracic glands (25 pairs) and integument (10 integuments) of larvae at age E1 (larval age when there is no BhC4-1 expression in the salivary gland) and at age E7 + 4 h (larval age when BhC4-1 is maximally expressed in the salivary gland) (Basso et al, 2002). The dissected tissues were washed twice in 70% ethanol and total RNA was extracted as previously described (Candido-Silva and Monesi, 2010). Total RNA concentrations were estimated by absorbance measurements at 260 nm, assuming that 40 lg/mL RNA has an absorbance of 1.0.…”
Section: Rna Extractionmentioning
confidence: 99%
See 3 more Smart Citations
“…Total RNA was isolated from salivary glands (10 pairs), prothoracic glands (25 pairs) and integument (10 integuments) of larvae at age E1 (larval age when there is no BhC4-1 expression in the salivary gland) and at age E7 + 4 h (larval age when BhC4-1 is maximally expressed in the salivary gland) (Basso et al, 2002). The dissected tissues were washed twice in 70% ethanol and total RNA was extracted as previously described (Candido-Silva and Monesi, 2010). Total RNA concentrations were estimated by absorbance measurements at 260 nm, assuming that 40 lg/mL RNA has an absorbance of 1.0.…”
Section: Rna Extractionmentioning
confidence: 99%
“…BhC4-1 transcript levels were normalized to Bh28S transcript levels, which do not vary during the larval stage (Monesi et al, 2001). Previous characterization of the BhEF1A-F1 gene has shown that it is not amplified during the larval stage (Candido-Silva and Monesi, 2010), and this gene was chosen for normalizing the BhC4-1 amplification levels in the genomic DNA samples. The presented data were obtained from at least two independent biological samples.…”
Section: Real Time Polymerase Chain Reaction (Qpcr)mentioning
confidence: 99%
See 2 more Smart Citations
“…Bradysia impatiens has been reported to be an economically problematic species in Florida (Mead, 1978), Bradysia species are known major insect pests in greenhouses (Meers and Cloyd, 2005), and Bradysia odoriphaga Yang and Zhang is the most serious pest of Chinese chive (Li et al, 2007). Bradysia hygida, first described by Sauaia and Alves (1968), is a sciarid that has been extensively used as a model system to study developmentally regulated gene transcription and amplification (Laicine et al 1984;Monesi et al 1995;Fiorini et al, 2001;Basso Jr et al, 2002;Candido-Silva and Monesi, 2010;Garcia et al, 2011;Passos et al, 2012). In this sciarid, the 5S ribosomal gene is localized in the autosomal A chromosome.…”
Section: Introductionmentioning
confidence: 99%